Peningkatan Prestasi Belajar PKn melalui Model Pembelajaran Kontekstual pada Siswa Kelas V Sekolah Dasar Sumberwungu II Tepus Gunungkidul - Antonius Eko Budiarto; Esti Setiawati (UM Purwokerto Press, 2022)
This study aims to improve Civics learning achievement through a contextual learning model for fifth grade students at SD Sumberwungu II Tepus, Gunungkidul Regency. The subjects in this study were 10 fifth grade students of SD Sumberwungu II Tepus, Gunungkidul Regency. Data collection methods used are observation and tests. This classroom action research was carried out in three cycles. Each cycle passes through four stages, namely planning, implementation, observation and reflection. Each cycle is carried out by giving action in groups, then one of the group representatives presents the results of group discussions, and the teacher concludes the results of student presentations. The data analysis method used is descriptive quantitative with percentage technique. The results showed that there was an increase in Civics learning achievement in fifth grade students of SD Sumberwungu II Tepus, Gunungkidul Regency, with an average mastery of learning achievement in the pre-cycle 37.8%, the end of the first cycle 40%, the end of the second cycle 50%, and the end of the cycle. III by 90%.